Application of the Problem-based Learning Model to Improve the Class V Elementary Student Learning Outcomes - Sitorus, Regina; Silaban, Patri Janson; Raja, Bogor Lumban; Ambarwati, Nova Florentina; Sitepu, Anton (JURNAL PAJAR (Pendidikan dan Pengajaran), 2024)
This study aims to improve student learning outcomes on the theme of heat and its transfer to the sub-theme of temperature and heat by applying the Problem-based Learning model for class V of SD Negeri 091585 AFDELING 7 DOSIN. The research type is Classroom Action Research. The research subjects involved 24 class V students. Based on the research results, it shows that there is an increase in student learning outcomes by implementing the Problem-based Learning model. This can be seen from the increase in student learning outcomes. Of the initial test (pretest), the student learning results were obtained before implementing the Problem-based Learning model. There were three people who completed it with a percentage of 12.5% while 21 people did not complete it with a percentage of 87.5% and an average of 37.95. In the first cycle, the observations of teacher activities were obtained at 52% while observations of student activities were obtained at 50%, there were 11 students who completed their learning outcomes with a percentage of 45.83% and 13 students who did not complete it with a percentage of 54.17%, and with an average value of 59.95. In cycle II, teacher activity observations were obtained at 88% while student activity observations were obtained at 90%. There were 19 students who completed their learning outcomes with a percentage of 79.17% and five students who did not complete it with a percentage of 20.82% with an average value of 73.45. This shows that there is a significant positive influence from the use of the Problem-based Learning model on student learning outcomes in theme heat and its transfer in class V at SD Negeri 091585 AFDELING 7 DOSIN in the academic year 2022/2023.